Shiva Temple (Temple 1) of the first cluster in the complex - Temples of India Project Team (Jio Institute, 2024)
Shiva Temple (Temple 1) is part of the first cluster in the complex and comprises three temples. The temple is dedicated to Shiva and dates to the first quarter of the 10th century CE. It currently has a garbhagriha (sanctum sanctorum) and antarala (vestibule), but the foundation and architectural remains of the temple suggest that originally, on plan, it also had a mandapa (pillared hall) and a mukhamandapa (front porch).